Enantioselective Synthesis of cis- and trans-Borocyclopropylmethanol: Simple Building Blocks To Access Heterocycle-Substituted Cyclopropylmethanols - Siddiqui, Saher H.; Navuluri, Chandrasekhar; Charette, André B. (Synthesis, 2019)
An enantioselective and non-oxidative methodology was developed to obtain enantioenriched cyclopropyl boronates using a diethanolamine-promoted selective decomplexation of dioxaborolane. The non-oxidative decomplexation of the dioxaborolane ligand from the cyclopropylmethoxide species formed in the dioxaborolane-mediated Simmons–Smith cyclopropanation reaction provided the enantioenriched CIDA-based (CIDA = N-cyclohexyliminodiacetic acid) borocyclopropane in 92% yield and 95.6:4.4 er. A robustness screen has shown diethanolamine to be compatible with esters, carbamates and N-heterocycles, providing a tool to access enantioenriched cyclopropanes carrying not only base-sensitive but oxidizable functional groups as well. Diethanolamine was found to be compatible with the modified zinco-cyclopropanation reaction of allyl alcohol to remove residual dioxaborolane from the corresponding cis-N-heterocycle cyclopropylmethanol, thereby leading to improved yields.
Keywords: borocyclopropanes; heterocycles; Simmons–Smith reaction; zinco-cyclopropanation; cross-coupling